2022
DOI: 10.2147/dmso.s388620
|View full text |Cite
|
Sign up to set email alerts
|

Omentin as an Independent Predictor of Metabolic Syndrome and Obesity Among Adolescents in Northeast China

Abstract: We investigated the association of omentin with metabolic syndrome (MetS), MetS components, and obesity in adolescents. Methods: A total of 742 middle-school students from Liaoyang City were enrolled in this cross-sectional study using the stratified cluster sampling method. Clinical information and blood samples were collected, and serum omentin levels were measured using enzyme-linked immunosorbent assay. Results: Mean plasma omentin levels were lower in male than in female participants (88.25 (interquartile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The healthy subjects in the study by Luedde et al were younger than patients and their BMI was not reported, while in our study the cases and controls were age- and gender-matched and the BMI was not significantly different [ 42 ]. Since serum omentin-1 has been shown to be inversely related to BMI, this may have been a confounding factor in the study by Luedde et al [ 5 , 42 , 66 , 67 ]. Moreover, our patients had more severe diseases, as reflected by the higher APACHE II scores.…”
Section: Discussionmentioning
confidence: 99%
“…The healthy subjects in the study by Luedde et al were younger than patients and their BMI was not reported, while in our study the cases and controls were age- and gender-matched and the BMI was not significantly different [ 42 ]. Since serum omentin-1 has been shown to be inversely related to BMI, this may have been a confounding factor in the study by Luedde et al [ 5 , 42 , 66 , 67 ]. Moreover, our patients had more severe diseases, as reflected by the higher APACHE II scores.…”
Section: Discussionmentioning
confidence: 99%
“…Omentin is a newly identified adipokine; it is a protein with a body weight of 38 kDa. Omentin is predominantly expressed in visceral adipose tissue and is secreted mainly from stromal vascular cells rather than adipocytes [93]. The expression of omentin decreases in patients with obesity, insulin resistance, and diabetes mellitus.…”
Section: Omentinmentioning
confidence: 99%
“…So, omentin has been proposed as a MetS biomarker and a biomarker of endothelial dysfunction in patients with MetS [93]. It has been shown that the level of omentin does not change during treatment with valproate [94], but studies on this topic are also singular, requiring the further study of omentin as a potential metabolic biomarker of VPA-MetS.…”
Section: Omentinmentioning
confidence: 99%